Effect of the seed maturation stage and pre-germination treatments on emergence of Erythrina crista-galli L. - de Freitas, Thales Castilhos; Gomes, Gustavo Crizel; Guarino, Ernestino de Souza Gomes; Molina, Artur Ramos; Medeiros, Fabricio Sanches; Souza, Luiz Carlos da Silva; Miura, Adalberto Koiti; de Sousa, Letícia Penno; Cardoso, Joel Henrique (Iheringia, Série Botânica., 2020)
The main goals of this study were to verify the existence of integumentary seed dormancy in Erythrina crista-galli seeds from mature pods and evaluate the seedling emergence from newly collected seeds in two stages of physiological maturation. Methods of overcoming dormancy were tested by comparing seedling emergence rate, mean emergence time and emergence index, with treatments: TC – control; T1– sanded and soaked in water for 48 h; T2 – sanded and soaked in water for 24 h; T3 – soaked in water without heating at the initial temperature of 60 °C, until reaching room temperature; T4 – only sanded; T5 – immature seeds. The results indicate that: i) newly collected seeds from mature pods do not require treatment to overcome dormancy; ii) immature seeds have germination similar to newly collected mature seeds.